“Motherhood is a work in progress”: a qualitative longitudinal study of maternal subjectivity and well-being of women in the Bukhali trial in Soweto, South Africa - Neusa F. Torres; Daniella Watson; Lerato Mohlomi; Tsakani Hlungwani; Caitlin V. Gardiner; Noreth Muller-Kluits; Shane A. Norris; Catherine E. Draper; Michelle Pentecost (Frontiers in Global Women's Health, 2026)
Background Motherhood is a crucial yet understudied aspect of maternal health, especially in sub-Saharan Africa, where inequalities and focus on clinical outcomes impact care. The concept of maternal subjectivities and matrescence, has limited exploration in South African public health. This article uses qualitative longitudinal data from the Bukhali trial to examine the social dynamics that shape maternal identities among young women. Methods Sixty women, mostly single, aged 22–34, participated in multiple interviews from 2023 to 2025. Using Neale's (2021) approach, we created case profiles and selected four for detailed analysis. Data were analysed with inductive coding and longitudinal strategies. Results Women's experiences of motherhood revolve around four interconnected themes. The first involves the emotional rollercoaster of matrescence and motherhood, described as intense and unpredictable, with love, exhaustion, pride, and self-doubt happening simultaneously. The second theme highlights financial struggles and economic instability, common among those facing unemployment, informal work, or limited social grants. The third theme emphasises the necessity of sacrifice and re-evaluating personal ambitions, an everyday part of motherhood rather than an exception, requiring balance between personal goals and children's immediate needs. The fourth stresses the crucial role of social support: its presence is vital, while its absence can lead to feelings of isolation, postnatal depression, and parenting difficulties for single mothers. Conclusion Motherhood in Soweto is complex and influenced by structural constraints and change. The caregiver-earner dual burden reflects post-apartheid gendered labour, while kinship support varies, challenging assumptions of female solidarity. Participants valued health education related to trials but reported no support for motherhood transition. The study recommends maternal-centered programs that address women’s psychosocial needs, personal experiences, and combine emotional and peer support with medical care.